The Bali Health Office Strategies Formulating: Reflection on The New Public Management - Ni Wayan Purnama Dewi; A. A. N. Oka Suryadinatha Gorda (Institute of Computer Science (IOCS), 2021)
In strategic management, the top leadership of the organization has a central role in achieving organizational goals , although in the implementation will involve subordinates who are at the middle and low management levels. In setting goals and targets, there are performance indicators key that must be achieved by the Bali Province Health Office in achieving organizational goals . This research uses qualitativ e methods and sample selection with purposive sampling technique.Analysis of data by analyzing the results of observations, interviews, and documentation obtained were processed using the NVIVO 12 Plus software . The results of the data processing in the study concluded that there are 9 main nodes , among them the achievement of targets, the implementation process of Strategy Plan ( RENSTRA ) , implementation barriers, strategic plan programs, evaluation of achievements, infectious diseases , Dengue Hemorrhagic Fever (DHF ), performance indicators, implications of policy and Covid -19 Pandemic. There are main nodes of target achievement that dominate the data obtained by researchers which state that there are still problems and obstacles in the effort to achieve the targets of the predetermined main performance indicators. It is necessary to coordinate between top leaders and middle managers to low managers so that activities that have been prepared can be integrated with each other in order to support the achievement of the performance indicators set out in the performance agreement and RENSTRA.